1993
DOI: 10.1161/01.res.72.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of endothelium-dependent vasodilator capacity by Escherichia coli endotoxemia.

Abstract: Increased release of endothelium-derived relaxing factor/nitric oxide has been proposed as the final common pathway for vasodilator responses to gram-negative lipopolysaccharide (endotoxin). To test this hypothesis, we examined endothelium-dependent and endothelium-independent vasodilator agents in vascular smooth muscle isolated from guinea pigs 16 hours after injection of saline (control group) or induction of Escherichia coli endotoxemia; aortic rings (approximately 1 mm in diameter) were studied with stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 39 publications
10
63
0
1
Order By: Relevance
“…Selective impairment of endothelium-dependent vasodilation by LPS was first demonstrated in vitro. 19,20 In humans in vivo, this was first confirmed by Bhagat et al 3 in veins. Subsequently, Hingorani et al 4 demonstrated reduced endothelium-dependent vasodilation of resistance and conduit vessels after vaccination with Salmonella typhi in healthy volunteers.…”
Section: Discussionmentioning
confidence: 79%
“…Selective impairment of endothelium-dependent vasodilation by LPS was first demonstrated in vitro. 19,20 In humans in vivo, this was first confirmed by Bhagat et al 3 in veins. Subsequently, Hingorani et al 4 demonstrated reduced endothelium-dependent vasodilation of resistance and conduit vessels after vaccination with Salmonella typhi in healthy volunteers.…”
Section: Discussionmentioning
confidence: 79%
“…Impairment of endotheliumdependent vasodilation is present in inflammation and was demonstrated in vitro 23,24 and in resistance arteries of healthy humans challenged by different inflammatory stimuli. 13,25 Consistent with previous studies, LPS impaired the FBF response to ACh and NE, with preservation of the dilation to the vascular smooth muscle relaxant NTG.…”
Section: Discussionmentioning
confidence: 99%
“…These include the vasodilators, including NO and prostacyclin, and the vasoconstrictors, including endothelin, thromboxane A2, and platelet-activating factor (Wanecek et al, 2000). Impaired endothelium-dependent relaxations have been shown in blood vessels from endotoxemic animals (Parker and Adams, 1993;Umans et al, 1993;Myers et al, 1995;Wiel et al, 2000). Apart from anatomical injuries, such impairment observed in endotoxemic blood vessels may result from several mechanisms: alteration in endothelial cell surface receptors; modified signal transduction pathways such as receptor-eNOS uncoupling; altered function and expression of eNOS; changes in the pathways that lead to release of NO;…”
Section: Impaired Endothelium-dependent Vascular Relaxationsmentioning
confidence: 99%